A computer-based method for the assessment of body-image distortions in anorexia-nervosa patients. - Harari, D. (IEEE Transactions on information technology in biomedicine)
A computer-based method for the assessment of body-image distortions in anorexia nervosa and other eating-disorder patients is presented in this paper. At the core of the method is a realistic pictorial simulation of lifelike weight changes, applied to a real source image of the patient. The patients, using a graphical user interface, adjust their body shapes until they meet their self-perceived appearance. Measuring the extent of virtual fattening or slimming of a body with respect to its real shape and size allows direct quantitative evaluation of the cognitive distortion in body image. In a preliminary experiment involving 33 anorexia-nervosa patients, 70% of the subjects chose an image with simulated visual weight gain between 8%-16% as their "real" body image, while only one of them recognized the original body image. In a second experiment involving 30 healthy participants, the quality of the weight modified images was evaluated by pairwise selection trials. Over a weight change range from -16% to +28%, in about 30% of the trials, artificially modified images were mistakenly taken as "original" images, thus demonstrating the quality of the artificial images. The method presented is currently in a clinical validation phase, toward application in the research, diagnosis, evaluation, and treatment of eating disorders.